SITOLOGI DAN TIPE REPRODUKSI Pteris multifida Poir. (PTERIDACEAE) - Hastuti, Diah Virsa; Praptosuwiryo, Titien Ngatinem; Djuita, Nina Ratna (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
Cytological observations have been carried out by several researchers in South China, Japan, Ceylon, Hongkong, Himalaya and Java. The results from various regions showed that P. multifida had a fairly high genetic variation, namely diploid, triploid and tetraploid types. Therefore cytological and reproductive study on P. multifida from its geographical distribution areas need to be done. The objectives of this research were to observe the somatic chromosome number and reproductive type of P. multifida, and to recognize the relationship between morphological variation and its ploidy level as well as stomatal index. Plants were collected from several localities in Bogor. Ploidy level was determined by observing somatic chromosome number by using squash methods. Reproductive type was determined by counting spore number in each sporangium. Morphological characters examined were the stipe, lamina, pinnae, veins, and indusium. Observations of stomata and epidermis of leaves were done by making an incision paradermal leaf. Pteris multifida has two ploidy level and reproduction type, namely apogamous triploid (2n = 87) and sexual tetraploid (2n = 116). The two ploidy levels could not be distinguished based on morphological characteristics, but they can be differentiated by their epidermal cells number. Apogamous triploid has fewer number of epidermal cells, the sexual tetraploid has a greater number of epidermis.